Morphological characterization of mammalian Timeless in the mouse brain development. (March 2015) - Inaguma, Yutaka; Ito, Hidenori; Hara, Akira; Iwamoto, Ikuko; Matsumoto, Ayumi; Yamagata, Takanori; Tabata, Hidenori; Nagata, Koh-ichi
Highlights: We prepared a specific antibody for Tim. In Western blotting, Tim was detected throughout the developmental stage. Immunohistochemistry revealed characteristic Tim distribution. Tim-mRNA distribution was similar to that of the protein. Abstract: Timeless was originally identified in Drosophila as an essential component of circadian cycle regulation. In mammals, the ortholog of Timeless (Tim) has also implicated in cell cycle control and embryonic development. In this study, we generated a specific antibody against Tim, and carried out expression and localization analyses of Tim during mouse brain development. In Western blotting, Tim was detected throughout the developmental stage. In immunohistochemical analyses, Tim was detected strongly in neurons in the ventricular zone/subventricular zone and moderately in cortical neurons during corticogenesis. In adult mouse brain, Tim was observed moderately in cortical neurons. Notably, Tim was enriched in the nucleus of cortical neurons from embryonic to early postnatal stages while it was distributed in the cytoplasm in the adult stage. Similar distribution change from nucleus to cytoplasm was observed in the hippocampal neurons between P0 and P30. In situ hybridization revealed that the tissue expression profile of Tim-mRNA was similar to that of the protein. In differentiated primary cultured mouse hippocampal neurons, Tim was detected in cell body, axon and dendrites. The obtained results suggest that Tim is expressed in neuronal tissues in a spatiotemporally regulated manner and involved in developmental stage-specific neuronal functions.